Evaluating Institutional Grants at African Universities - Andoh, Harris (International Higher Education, 2019)
The new missions of African universities—coping with massification, becoming research intensive, and attaining world-class status—require tremendous amounts of funding. Most African governments have chosen to provide their public universities autonomy to secure foreign grants from national governments, universities in developed countries, the international donor community, and philanthropic organizations. However, the impact of these initiatives is difficult to measure, given that most universities lack proper institutional evaluation mechanisms to record and track the outcomes of such projects/programs after they are completed. This article seeks to promote institutional evaluation as a critical tool for decision-making on performance improvement in order to assure better value for money in African universities.